ANALISIS PENGARUH SISTEM REWARD, JOB RELEVANT INFORMATION (JRI) DAN MANAGER VALUE ORIENTATION TOWARD INNOVATION (VOI MANAGER) TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Laswitarni, Ni Ketut; Gunastri, Ni Made (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
The purpose of this study are: (1) to analyze the system reward on the performanceemployees PT Ellora Bali; (2) to analyze Job Relevant Information (JRI)on the performance employees PT Ellora Bali; (3) to analyze Manager Value Orientation Toward Innovation (VOI Manager)on the performance employees PT Ellora Bali; (4) to analyzeon job satisfaction of performance employees PT Ellora Bali;(5) to elucidate the role of job satisfaction in mediating the effects of thesystem rewardon the performance of employees PT Ellora Bali; (6) to elucidatethe ruleof job satisfaction in mediating effects of the JRI on the performance of employees PT Ellora Bali ; (7) to elucidate the role of job satisfaction in mediating the effects of the VOI Manager on the performance of employees PT Ellora Bali.Total population in this study were as many as 78 employees PT Ellora Bali. Data analysis of this study using SPSS for windows 16 and Path Analysis. The results this study showed that: 1) System reward has significant effect on performance employees; 2) JRI has significanteffect on employee performance; 3) VOI Manager has significant effect on employee performance; 4) Job satisfaction has significant effect on employee performance; 5) System reward has a significant direct effect on employee performance through the mediation of job satisfaction ; 6) JRI has a significant direct effecton employee performance through the mediation of job satisfaction; 7) VOI Manajer has a significant direct effect on employee performance through the mediation of job satisfaction.